Challenges and Coping Strategies of Night Junior High School Learners in Learning Sequences and Series Through Mathematics in a Box - Amoto, Jeena A. (Jurnal Multidisiplin Madani, 2023)
This research aimed to explore the challenges and coping strategies of night junior high school learners in learning sequences and series through Mathematics in a Box. It involved a case study of a class of grade 10 Night Class learners in the Philippines. The principles of constructionism and symbolic interactionism backed up the thematic analysis of the data. During a six-week conversation, classroom observations and journal writing were done. Five learners participated in one-on-one interviews, and 10 in focus group interviews. Participants struggled with understanding, intricacy of rules, misconceptions, and with personal circumstances. Their coping strategies: dissecting the problem; speaking in a comfortable language; doing independent study; and reflecting on their answer. There is potential in using mathematics in a box to address challenges while learning sequences and series